2018
DOI: 10.2298/mpns18s1059m
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of application and level of nurses’ knowledge on administering intramuscular injections into the ventrogluteal site

Abstract: Introduction. The most recent literature data and studies have recommended the middle gluteal muscle or the ventrogluteal side as the site for the application of intramuscular injection. Although it has been recommended for many years because of its many advantages it is rarely used in the clinical practice. The aim of this study was to evaluate the frequency of application of intramuscular injection and the level of nurses' of knowledge on how to give injections at the ventrogluteal site. Material and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…In the present study, although the vast majority of the nurses knew that the use of VG site was recommended as the IM injection site, more than half of them administered IM injection into the DG site (Kaya et al, 2016; Turan et al, 2019), which is similar to the national and international literature (Eroğlu & Çevik, 2019; McGee, 2017; Sarı et al, 2017; Strohfus et al, 2018). In the study of Milutinović et al (2018) in Serbia, 20.8% of the nurses use the VG site during clinical practices. The reasons why nurses mostly preferred the DG site in IM practices include the working department, experience time in the department, learning nursing practices in working life by master‐apprentice relationship, inability and unwillingness to access and use up‐to‐date information, patients' refusal of procedures to this site because of not being accustomed to the VG site, and patients' thought that they will feel more pain (Arslan & Özden 2018; Sarı et al, 2017; Turan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, although the vast majority of the nurses knew that the use of VG site was recommended as the IM injection site, more than half of them administered IM injection into the DG site (Kaya et al, 2016; Turan et al, 2019), which is similar to the national and international literature (Eroğlu & Çevik, 2019; McGee, 2017; Sarı et al, 2017; Strohfus et al, 2018). In the study of Milutinović et al (2018) in Serbia, 20.8% of the nurses use the VG site during clinical practices. The reasons why nurses mostly preferred the DG site in IM practices include the working department, experience time in the department, learning nursing practices in working life by master‐apprentice relationship, inability and unwillingness to access and use up‐to‐date information, patients' refusal of procedures to this site because of not being accustomed to the VG site, and patients' thought that they will feel more pain (Arslan & Özden 2018; Sarı et al, 2017; Turan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one‐third of the nurses indicated that they did not know the administration of injection into the VG site. Similarly, in the study of Milutinović et al (2018) in Serbia, 32.6% of the nurses indicated that they were not adequately informed about the use of the VG site (Mılutınovıć et al, 2018). It is expected that it should be taught that the use of the VG site should be preferred for IM injections during nursing education (Soliman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Tais incongruências nos achados entre os artigos avaliados podem refletir uma abordagem não padronizada de como os enfermeiros são inicialmente ensinados o que, posteriormente, pode repercutir em suas práticas profissionais em relação à administração de medicamentos via IM. [51][52][53][54][55][56] Portanto, o currículo de enfermagem deve ser revisto de forma consistente baseado em tecnologias avançadas e altos níveis de evidências científicas 57 para evitar a lacuna entre a teoria e a prática relacionada à educação e aplicação da assistência de enfermagem. 58 Estudo realizado com enfermeiros atuantes em uma instituição hospitalar no interior de Minas Gerais identificou déficits de conhecimento em questões essenciais para a administração de medicamentos segura, dentre elas, àquelas relacionadas à obtenção de informações e conhecimento em administração de medicamentos.…”
Section: Discussionunclassified
“…Currently, there is little if any updated evidence‐based IM injection education related to sex or BMI in organisations in which nurses are employed (Milutinović, 2018; White et al, 2018). IM injection technique and muscle landmark training based on evidence are rarely available in healthcare settings (Carter‐Templeton & McCoy, 2008; Cocoman & Murray, 2010; Davidson & Rourke, 2013; Strohfus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%